2016
DOI: 10.1113/jp271925
|View full text |Cite
|
Sign up to set email alerts
|

Genetic alteration of the metal/redox modulation of Cav3.2 T‐type calcium channel reveals its role in neuronal excitability

Abstract: Key pointsr In this study, we describe a new knock-in (KI) mouse model that allows the study of the H191-dependent regulation of T-type Cav3.2 channels. Sensitivity to zinc, nickel and ascorbate of native Cav3.2 channels is significantly impeded in the dorsal root ganglion (DRG) neurons of this KI mouse. Importantly, we describe that this H191-dependent regulation has discrete but significant effects on the excitability properties of D-hair (down-hair) cells, a sub-population of DRG neurons in which Cav3.2 cur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 69 publications
0
10
0
Order By: Relevance
“…In order to evaluate whether T-type channels would be regulated by a rise in intracellular Ca 2+ ([Ca 2+ ] INT ), we first used the Ca 2+ ionophore ionomycin. In D-hair mechanoreceptor sensory neurons, which specifically express a high density of T-type channels ( Shin et al, 2003 ; Dubreuil et al, 2004 ; Voisin et al, 2016 ), extracellular perfusion of 10 µM ionomycin induced a potent decrease of the T-type current ( Figure 1a ). This current inhibition (~85% in average) occurred in the minute range ( Figure 1b ) and was associated with a large hyperpolarizing shift in the steady-state inactivation curve (~22 mV, p < 0.001, Figure 1c ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In order to evaluate whether T-type channels would be regulated by a rise in intracellular Ca 2+ ([Ca 2+ ] INT ), we first used the Ca 2+ ionophore ionomycin. In D-hair mechanoreceptor sensory neurons, which specifically express a high density of T-type channels ( Shin et al, 2003 ; Dubreuil et al, 2004 ; Voisin et al, 2016 ), extracellular perfusion of 10 µM ionomycin induced a potent decrease of the T-type current ( Figure 1a ). This current inhibition (~85% in average) occurred in the minute range ( Figure 1b ) and was associated with a large hyperpolarizing shift in the steady-state inactivation curve (~22 mV, p < 0.001, Figure 1c ).…”
Section: Resultsmentioning
confidence: 99%
“…All animal use procedures were done in accordance with the directives of the French Ministry of Agriculture (A 34-172-41). Dorsal root ganglion (DRG) neurons were prepared as described earlier ( Voisin et al, 2016 ). Briefly, adult male C57BL/6J mice were anaesthetized with pentobarbital injection and transcardially perfused with HBSS (pH 7.4, 4°C).…”
Section: Materials and Methodsmentioning
confidence: 99%
“…Besides ethosuximide, Zonisamide and Z944 also have been recruited in the preclinical trial for pain treatment (Zamponi, 2016 ). Up to now, Ni 2+ is still the most often used T-type channel blockers for animal experiments, possibly due to its high efficiency and reversible action (Chen et al, 2015 ; Voisin et al, 2016 ; Zhang et al, 2017 ). We observed that NiCl 2 (0.2 mM) decreased the amplitude of T-type calcium current to 29.6 ± 4.6% of control in SG neurons, which was lower than that of the observation in lamina II–V SDH neurons (Ryu and Randic, 1990 ), possibly due to the different holding potential (−90 mV in Ryu’s study vs. −110 mV in our study) used.…”
Section: Discussionmentioning
confidence: 99%
“…3B). DRG neurons were exposed to factors secreted from G-CSF-primed microglia cells for a further 16 h, after which both spontaneous and evoked neuronal activity was recorded by patch clamp electrophysiology (26,27). As shown in Fig.…”
Section: G-csf Conditions Microglia To Sensitize Drg Neurons Throughmentioning
confidence: 99%